Coccoloba tunii (Polygonaceae), a new species from Chiapas (Mexico) - Ortiz-Díaz, Juan Javier; Arnelas, Itziar; Pinzón, Juan P. (Phytotaxa, 2016)
Coccoloba tunii is here described as a new species from Mexico. Morphological characters of the leaf, inflorescence, and fruit show discontinuities among populations of C. tunii and its relative, C. liebmannii. In addition, both species exhibit different geographical patterns, C. tunii is exclusive of the Central Depression and Plateau of Chiapas (Mexico) at mid elevations, while C. liebmannii ranges from Oaxaca to Colima on lowlands along the Pacific watershed.